Digital Technologies Applied in Agriculture for Sustainable Development - Radulescuu, Carmen-Valentina; Popescu, Maria-Loredana; Oancea Negescu, Mihaela Diana; Bodislav, Dumitru Alexandru (European Journal of Sustainable Development, 2019)
Recently, many articles deal with Internet and mobile phones that have penetrated all sectors of the economy, including agriculture, in the light of their benefits. Various reports, including the World Bank, describe the main benefits of new information and communication technologies and promote their greater integration into the wider economy to increase efficiency by completing other production factors and fostering innovation, for example, drastically reducing transaction costs. The article analyzes recent literature but also presents novelty elements that emerged from questions such as the risks associated with new technologies considering that there are not enough studies in the field confirming, on the one hand, the benefits but also the losses caused by them. Keyword: New technology, agriculture, innovation